2018
DOI: 10.21277/sw.v1i8.359
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sports on paralympic athletes’ personal development

Abstract: One of the most effective ways of integrating people with disabilities into society and ensuring their comprehensive personal development is to engage people with disabilities into Paralympic Games. Such engagement creates the necessary conditions to socialize people with disabilities, to adapt their physical and mental states to existing living conditions, to ease negative manifestations of their psycho-emotional states, to promote their self-realization. The article presents the results of the research deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the systematic review process, we identified twenty-seven studies: twelve from Europe (Italy [66,79], Ireland [68], UK [59,63,78,80], Poland [7], Portugal [74], Turkey [65] and Ukraine [69,70]), ten from North America (USA [47,60,72,73,[81][82][83] and Canada [64,67,75], three from South America (Brazil [61,62] and Chile [77]), one from Asia (Indonesia [76]) and one from Oceania (Australia [71]).…”
Section: Originmentioning
confidence: 99%
“…The samples of the studies reviewed include the following groups of sports: two from wheelchair basketball [36,72], three from swimming [59,66,79], three from wheelchair rugby [47,60,68], one from ice skating [65], one from wheelchair tennis [80] and seventeen from multiple sports [7,26,[61][62][63][64]67,[69][70][71][73][74][75][76][77][78]82]. At least nine samples are from Paralympic athletes.…”
Section: Sports Participantsmentioning
confidence: 99%
“…The positive impact of sport on people with disabilities consistently influences psychological well-being and can change lives for the more positive (Haslett et al, 2017;Kane et al, 2016;O. Kokun et al, 2021;O. M. Kokun et al, 2018;Puce et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that involvement in wheelchair sports can change perceptions of disability (Carter et al, 2014; Moss et al, 2020) and foster personal growth among individuals with disabilities (Kokun et al, 2018; Richardson et al, 2017). To investigate the relationships between wheelchair tennis participation and psychosocial wellbeing, Richardson et al (2017) interviewed 16 people with physical disabilities.…”
Section: Recreational Therapy (Rt) and Adaptive Recreational Sportsmentioning
confidence: 99%
“…Players expressed appreciation for developing a diverse range of physical abilities through sports participation and for the atmosphere of acceptance among peers regardless of their disabilities. In an examination of the impact of adaptive sports on Paralympic athletes’ personal growth, Kokun et al (2018) found that individuals who engaged in high levels of adaptive sports showed a higher degree of purpose in life and self-acceptance than those who did not.…”
Section: Recreational Therapy (Rt) and Adaptive Recreational Sportsmentioning
confidence: 99%